Tourism and leisure research methods : data collection, analysis and interpretation - Finn, Mick.; Elliott-White, Martin; Walton, Mike. (Harlow [England] : Pearson Education, 2000)
This book is about: Methodology and research design; Evaluating research; Secondery data analysis in leisure and tourism research; Quanlitative methods; ...
Keywords: Tourism; Leisure; Leisure; Tourism -- Research -- Methodology